LEGISLATIVE FOUNDATIONS OF INHERITANCE LAW IN UZBEKISTAN - Камардинов Хумоюн Камардин огли (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2026)
Annotation. This article examines the rules of inheritance by law in the Republic of Uzbekistan. It delves into the legal framework governing inheritance, focusing on the key principles and regulations outlined in the Uzbek Civil Code. The article provides an overview of the different categories of heirs, the order of succession, and the distribution of the deceased’s estate. Additionally, it explores the procedures for claiming inheritance rights and addresses potential legal issues that may arise during the inheritance process. By highlighting the specificities of Uzbek inheritance law, this article aims to provide a comprehensive understanding of how inheritance is regulated and implemented within the country.